Unsur Tasawuf Akhlaki Dalam Novel Ayat-Ayat Cinta 1 dan 2 Karya Habiburrahman Elshirazy - Nesia Mu’asyara; Muhtadin Muhtadin (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
Sufism as one of the Islamic scientific fields has several stages of training (riyadhah) in order to get as close as possible to Allah SWT, so that through this iriyadhah you will give birth to lakhlak al ikarimah. The novel Ayat-Ayat Cinta 1 and 2 by iHabiburrahman El Shirazyi is a soul-building literary work that is strong in spiritual values ​​and full of jtasawuf values. Love 1 and 2 by Habiburrahman1 El! Crazy! as! work! literature! which is so famous in Indonesia because it is full of spiritual values, so that not a few people are enlightened. This research is library research, which is a type of research that refers to the treasures of literature, including books, essays, theses and other documents. Data collection in this research used philosophical descriptive research methods and to analyze the data in this research used historical descriptive methods, content analysis and interpretation. And in drawing conclusions, researchers used deductive methods. Apart from that, this research has a formal Sufism object and the novel Ayat-Ayat Cinta 1 and 2 by Habiburrahman Eli Shirazyl as its immaterial objects. The results of this research are: 1). The novel `Ayat-ayat Cintai' by Habiburrahman l El Shirazy contains 1 Sufism values, 2). The Sufism values ​​contained in the novel Ayat-Ayat Cintai by; Habiburrahman; El Shiazyi contain characteristics of Sufism; ;akhlaqi.